2015
DOI: 10.1021/acs.jmedchem.5b01399
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanism of Cytotoxicity for the Selective Selenosemicarbazone, 2-Acetylpyridine 4,4-Dimethyl-3-selenosemicarbazone (Ap44mSe): Lysosomal Membrane Permeabilization

Abstract: Selenosemicarbazones show marked antitumor activity. However, their mechanism of action remains unknown. We examined the medicinal chemistry of the selenosemicarbazone, 2-acetylpyridine 4,4-dimethyl-3-selenosemicarbazone (Ap44mSe), and its iron and copper complexes to elucidate its mechanisms of action. Ap44mSe demonstrated a pronounced improvement in selectivity toward neoplastic relative to normal cells compared to its parent thiosemicarbazone. It also effectively depleted cellular Fe, resulting in transferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 74 publications
3
29
0
Order By: Relevance
“…Although the Cu complex of Dp44mT showed similar antiproliferative activity to its free ligand, Donepezil in the presence of Cu demonstrated increased antiproliferative activity relative to Donepezil alone ( Table 1). As shown previously [62], the Fe complexes of DFO and Dp44mT showed significantly (p < 0.001) decreased anti-proliferative activity compared to their respective ligands ( Table 1). The anti-proliferative efficacy of Donepezil in the presence of iron was similar to that observed for Donepezil alone (>100 µM; Table 1).…”
Section: A N U S C R I P Tsupporting
confidence: 83%
See 1 more Smart Citation
“…Although the Cu complex of Dp44mT showed similar antiproliferative activity to its free ligand, Donepezil in the presence of Cu demonstrated increased antiproliferative activity relative to Donepezil alone ( Table 1). As shown previously [62], the Fe complexes of DFO and Dp44mT showed significantly (p < 0.001) decreased anti-proliferative activity compared to their respective ligands ( Table 1). The anti-proliferative efficacy of Donepezil in the presence of iron was similar to that observed for Donepezil alone (>100 µM; Table 1).…”
Section: A N U S C R I P Tsupporting
confidence: 83%
“…The anti-proliferative activity of the copper and iron complexes of the controls, DFO, Dp44mT and Donepezil, were also assessed. The Cu complex of DFO showed a significant (p < 0.001) increase in anti-proliferative activity relative to the free ligand, as observed previously [62]. Although the Cu complex of Dp44mT showed similar antiproliferative activity to its free ligand, Donepezil in the presence of Cu demonstrated increased antiproliferative activity relative to Donepezil alone ( Table 1).…”
Section: A N U S C R I P Tsupporting
confidence: 81%
“…As shown in Figures 8C and 8D, a significant intracellular red dot fluorescence was observed due to the formation of protonated AO in the intact lysosomes (pH 4–5), implying that 3 and 5 did not damage the lysosomes in dark. However, the intracellular red fluorescence was weakened or even disappeared under light irradiation, which demonstrated that AO was released from the lysosome into the cytoplasm (pH ∼7.2), and moreover, deprotonated in the weak alkaline environment to emit diffuse green fluorescence (Al-Eisawi et al., 2016, Boya and Kroemer, 2008). This observation suggested that 3- and 5 -triggered 1 O 2 can induce LMP, and effectively promoted cell death via lysosome-associated pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The anticancer and antioxidant activities of thiosemicarbazones are clearly affected by their structural formulae and interaction with metals [130,131,132]. The antiproliferative activity of the ligands HPTSC and HPTSC* and their Cu II complexes has been evaluated after 24 h of drug treatment, using MTT assay and the results are summarized in Table 3 cellular line, where the compound 1 showed higher value of cytotoxicity than compound 2 [37].…”
Section: Biological Activitymentioning
confidence: 99%